Sex as a moderator of the relationship between hip abduction strength and muscle activation during single-leg stance - Rodrigo Rodrigues; Francesca Chaida Sonda; Michele Fernandes Frigotto; Pablo Gaviraghi; Talita Molinari; Nicolas da Silva Pereira; Matheus Iglesias Marques; Rodrigo Freire Guimarães; Eduarda Bastos Cabral; Rodrigo Rabello (PLoS ONE, 2025)
Background Single-leg stance requires pelvic stability, largely supported by the hip abductors. Differences in hip abductor activation between sexes and individuals with or without musculoskeletal conditions may relate to abductor weakness. However, the relationship between hip abduction strength and muscle activation during stance, and whether this is moderated by sex, remains unclear. Objective To investigate whether maximal hip abduction strength is associated with hip abductor EMG amplitude during single-leg stance, considering sex as a moderator. Methods Thirty-six adults (18 males, 18 females) performed an estimated 1RM side-lying hip abduction test and two 10-second single-leg stance trials. EMG amplitude of the gluteus medius (GMed) and tensor fasciae latae (TFL) was analyzed. A moderation analysis (PROCESS Model 1) was used to test the interaction between strength and sex. Results Hip abduction strength, sex, and their interaction explained 51% of the variance in GMed EMG amplitude (R2 = 0.51; p < 0.001). A significant strength × sex interaction were observed (p = 0.002). Females with lower strength showed greater GMed activation (p < 0.001); this was not seen in males (p = 0.24). No significant effects were found for TFL activation (R2 = 0.02; p = 0.89). Conclusion Females with lower hip abduction strength demonstrate greater GMed activation during single-leg stance, suggesting a sex-specific compensatory strategy. No similar effect was observed for TFL. These findings highlight the importance of considering sex in neuromuscular assessments of pelvic stability.